Regulatory Testing of Home Appliances - Mattoo, Harish (My University, 2022)
LG Electronics provides a great platform for the budding engineers to gain a valuable experience in such a large industry and that too in a friendly cultured way. Although the enormous amount of work done and experience gained in the past one-year can’t be just listed in a few lines but here is an overview of the training. The objective of the project is “REGULATORY TESTING OF HOME APPLIANCES” which gives the reader an overview of the MWO technology, Refrigerator & Room Air Conditioner. At R&D (Development Planning) LGEIL, my work mainly consisted of product testing & certification according to international industry standards specified by Government of India. The report is divided into different sections emphasizing on every field. It tells the reader about the profile and portfolio of LG Electronics. Further, the history, working, nomenclature, major parts etc. of Microwave Oven are discussed in detail. Then the testing and procedure of product certification (MWO, REF & RAC) according to BEE (Bureau of Energy Efficiency) are detailed. The report is wound up discussing about the Indian & International Standards and their importance & relevance.
ME Power system
Keywords: Bureau of energy efficiency; Bureau of Indian standards; Endurance test; Suction guide